Difference in Dietary Factors in Young Females with and Without Polycystic Ovarian Disease - Nida Azeem, Beenish Riaz, Huma Afridi, Wajiha Shadab, Itaat Ullah Khan Afridi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Although diet has an important role in blood glucose and insulin regulation, there is little study on dietary therapy of “polycystic ovarian syndrome”, abbreviated as PCOS. So this research work was done to look at some particular dietary components, which may predispose development of PCOS. Aim: To compare the mean value of intake of dietary of daily meal in young females with and without PCOS Main outcome measures: Mean white bread and potatoes servings per last 7 days Study design: Case control study Duration of study: 6 months from January 2022 to June 2022 Setting: Study was conducted at Sialkot Medical College Sialkot” affiliated with Imran Idrees Teaching Hospital in Obstetrics /Gynecology department over the period of 6 months from January 2022 to June 2022 Method: Total 84 female were included in the stud and divided in two equal groups i.e. females with PCOS and females without PCOS. They were asked about their dietary pattern and total intake of potatoes and bread they consume per week was noted. SPSS was used to compare both groups for mean dietary intake Results: In case group, the mean intake of white bread was 7.55±1.74 while in control group was 5.5±1.9 (P < 0.05) while mean potato serving in cases was 6.62±2.39 in cases while 3.48 ±1.74 in controls (P < 0.05). Practical implication. All patients with PCOS who are attending the gyne clinics should be counselled about diet and life style modifications that has a crucial role in treating the disease. .A diet low in saturated fat and high in fibre from predominantly low-glycaemic-index-carbohydrate foods is recommended for patients with PCOS. The dietary management of women suffering from PCOS should be carried out by registered dietitians, gynecologists, fertility specialists, and endocrinologists from the time of diagnosis to help patients recognize the role of diet and lifestyle changes how these can be altered through nonpharmacological means to improve prognosis. Conclusions: Thus females having PCOS showed more intake of potatoes and breads. Keywords: Polycystic Ovarian Syndrome, Dietary factors, life style, bread, potatoes